Religion and Ethics in Schopenhauer - Ito, Takao (Voluntas: Revista Internacional de Filosofia, 2022)
Schopenhauer’s theory of religion is mainly discussed in his ethics. Therefore, conventional studies often argue that Schopenhauer made an attempt to make a rational justification of religion through the process of recognising the reason for religion’s existence in its ethical values. However, his theory of religion contains other aspects which cannot be discussed soley in terms of the above view, for he not only observed subtle differences between religion and ethics but even considered that religion could go against ethics at times. For this reason, we cannot simply say that Schopenhauer used ethics as a means to make a rational justification of religion. Rather, he viewed ethics as a standard for criticising religions, though he did not deny religion. He neither affirmed nor denied religion. Based on his ethics, he simply engaged in a philosophical analysis of a human activity called religion as he considered such an approach to be the appropriate one for a philosopher. On that account, what is important here is where in religion Schopenhauer saw the conditions for ethical values. From that point of view, this paper reinterprets his thought through descriptions in his major work, The World as Will and Representation, with an intention to offer a new reading of Schopenhauer’s theory of religion.